Description of the Characteristics of Parents on the Level of Anxiety of Parents whose Children are Cared for in the PICU Room of Dr. Wahidin Sudirohusodo Hospital Makassar - Nour Sriyanah; Suradi Efendi; Sri Mulyani (International Journal of Public Health Excellence (IJPHE), 2022)
Based on the research results Helena (2008) conclude from the 11 respondents who had a good knowledge gained 7 respondents experiencing mild anxiety (63.6%), 3 respondents had moderate anxiety (27.2%) and 1 respondent suffered from severe anxiety (9.1 %). The purpose of this study is to know description of characteristics of parents towards anxiety level of parents whose children were hospitalized in PICU. This was descriptive research. This study will describe association between parents; characteristics and anxiety level. The result showed that of the 40 samples studied based on the characteristics of sex, male sex as many as 7 people (17.5%) and female sex as many as 33 people (82.5%), the characteristics of age, it was shown younger age group as many as 14 people (35.0%) and older age group as many as 26 people (65%), obtained with low education as many as 10 people (25.0%) and high education as many as 30 people (75%), all respondents work (100%) or 40 respondents. The level of parental anxiety, experiencing mild anxiety level as many as 16 people (40%), anxiety levels were as many as 14 people (35%) and severe anxiety level as many as 10 people (25%). Expected in the implementation of nursing and medical measures should still pay attention to the principle of the provision of information and education of patients about the actions to be taken in order to better understand thus enhancing individual coping and reduce parental anxiety.